Verification of operational weather forecasts from the POSEIDON system across the Eastern Mediterranean - A. Papadopoulos; P. Katsafados (Copernicus Publications, 2009)
The POSEIDON weather forecasting system became operational at the Hellenic Centre for Marine Research (HCMR) in October 1999. The system with its nesting capability provided 72-h forecasts in two different model domains, i.e. 25- and 10-km grid spacing. The lower-resolution domain covered an extended area that included most of Europe, Mediterranean Sea and N. Africa, while the higher resolution domain focused on the Eastern Mediterranean. A major upgrade of the system was recently implemented in the framework of the POSEIDON-II project (2005–2008). The aim was to enhance the forecasting skill of the system through improved model parameterization schemes and advanced numerical techniques for assimilating available observations to produce high resolution analysis fields. The configuration of the new system is applied on a horizontal resolution of 1/20°×1/20° (~5 km) covering the Mediterranean basin, Black Sea and part of North Atlantic providing up to 5-day forecasts. This paper reviews and compares the current with the previous weather forecasting systems at HCMR presenting quantitative verification statistics from the pre-operational period (from mid-November 2007 to October 2008). The statistics are based on verification against surface observations from the World Meteorological Organization (WMO) network across the Eastern Mediterranean region. The results indicate that the use of the new system can significantly improve the weather forecasts.